A dawson-type polyacid plasma electron sponge hydrogen purification composite membrane, a preparation method therefor, and an application thereof
Patent Information
- Application Number
- CN202611410211.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-20
AI Technical Summary
受限于自身核结构,该类多酸的氧化还原活性位点数量匮乏,电子存储容量低,难以高效捕获并储存等离子体热电子,这使得膜表面电子密度调控幅度受限,对CO2的排斥调控能力存在固有上限,最终造成H2/CO2分离选择性难以提升,无法满足高选择性气体分离的应用需求,成为现有技术的核心短板
[0021]有益效果:与现有技术相比,本发明具有以下显著优点:(1)本发明Dawson型十八钼二磷酸(P2Mo18)等离子体电子海绵氢气纯化复合膜包括有自组装的Dawson型十八钼二磷酸(P2Mo18)等离子体电子海绵膜,Dawson型十八钼二磷酸(P2Mo18)等离子体电子海绵膜性能稳定,绿色环保且制备方法操作简单,条件温和易实现,克服了现有技术工艺复杂,可控性差的缺点。(2)本发明Dawson型十八钼二磷酸(P2Mo18)等离子体电子海绵氢气纯化复合膜在氢气纯化应用具有明显优势:
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane, its preparation method, and its application, particularly to a Dawson-type octadecylmolybdenum diphosphate (H6P2Mo) 18 O 62 P2Mo (abbreviated as P2Mo) 18 Plasma-electronic sponge hydrogen purification composite membrane and its preparation method, as well as its application in hydrogen purification and separation in mixed gases. Background Technology
[0002] Hydrogen is a clean energy carrier, and methane steam reforming is the mainstream industrial hydrogen production process. The resulting mixed gas contains H2, CO2, CH4, and water vapor impurities, requiring efficient separation and purification of hydrogen from acidic gases and alkane gases. Membrane separation technology is a highly promising hydrogen purification technology due to its low energy consumption and simple operation. Traditional static gas separation membranes have fixed pore and surface properties, relying on differences in molecular dynamics diameters to sieve gases. However, the kinetic diameters of H2 (0.29 nm) and CO2 (0.33 nm) are very similar, making it difficult to achieve high-selectivity separation by relying solely on size sieving.
[0003] Polyacids (POMs), also known as electron sponges, can achieve reversible, rapid, and multi-level electron storage while maintaining their crystal structure. Different configurations of POMs (Keggin type, Dawson type) inherently differ in electron storage capacity; moreover, the degree of reduction of the POM directly determines the actual number of electrons it can capture and store. Gold nanoparticles generate a localized surface plasmon resonance effect under specific wavelength illumination, producing a large number of hot electrons. If these hot electrons are directionally transferred to POMs for storage, the electron density distribution on the membrane surface can be dynamically changed, and selective gas transport can be achieved by utilizing the differences in polarizability of different gas molecules. The polarizability of CO2 is much greater than that of H2. The high electron density surface will repel the high polarizability CO2, while having little hindrance to the transport of low polarizability H2, thus significantly improving H2 selectivity.
[0004] Currently, the functional polyacid materials used in plasma-responsive gas separation membranes are mainly Keggin-type polyacids such as dodecylmolybdate phosphate and dodecyltungstic acid. Limited by their core structure, these polyacids have a limited number of redox active sites and low electron storage capacity, making it difficult to efficiently capture and store plasma hot electrons. This limits the range of electron density regulation on the membrane surface and imposes an inherent upper limit on the repulsion regulation ability against CO2. Ultimately, this makes it difficult to improve the selectivity of H2 / CO2 separation, failing to meet the application requirements of high-selectivity gas separation, becoming a core weakness of existing technologies. How to fully utilize the Dawson-type octadecylmolybdate diphosphate (P2Mo) is a key challenge. 18 The intrinsic multi-electron storage advantage enables the construction of high-performance Au@P2Mo. 18Overcoming the performance limitations imposed by Keggin-type polyacids is a major challenge that needs to be addressed in gas separation membranes. Summary of the Invention
[0005] Objectives of this invention: One objective is to provide a plasma-electron sponge hydrogen purification composite membrane with a Dawson-type polyacid as the core electron sponge. Dawson-type polyacids are crucial materials for achieving ultra-high selectivity. Utilizing the numerous redox sites in the Dawson structure, a large number of hot electrons generated by Au plasma are captured, resulting in extremely high electron density on the membrane surface. Ultra-high efficiency hydrogen separation is achieved through polarization differences. Another objective is to provide a method for preparing this composite membrane. This method employs liquid-liquid interface self-assembly, focusing on a preparation step with controllable polyacid reduction. The conditions are mild, the membrane thickness is controllable, and the problem of polyacid aggregation and precipitation is avoided. A final objective is to provide the application of this Dawson-type polyacid plasma-electron sponge hydrogen purification composite membrane in the purification of hydrogen mixtures produced by reforming, adaptable to actual working conditions involving the separation of gases containing water vapor impurities and multi-component mixed gases.
[0006] Technical solution: The present invention discloses a Dawson-type polyacid plasma electron sponge hydrogen purification composite membrane, comprising a self-assembled Dawson-type polyacid plasma electron sponge nanofunctional membrane and a macroporous support membrane, wherein some pores of the Dawson-type polyacid plasma electron sponge nanofunctional membrane are connected to some macropores of the macroporous support membrane.
[0007] The Dawson-type polyacid plasma-electron sponge nanofunctional membrane is composed of plasma nanoparticles and Dawson-type polyacids capable of storing electrons. The thickness of the Dawson-type polyacid plasma-electron sponge hydrogen nanofunctional membrane is 40-250 nm, preferably 127-250 nm, with 127 nm being the most optimal. The plasma nanoparticles are gold nanoparticles with a particle size of 5-35 nm, preferably 15 nm. The electron-storing Dawson-type polyacid is selected from octadecylmolybdenum diphosphate (P2Mo). 18 The macroporous support membrane is an anodic aluminum oxide membrane with a pore size of 40-100 nm, preferably 70 nm.
[0008] The preparation method of the plasma electron sponge hydrogen purification composite membrane with Dawson-type polyacid as the core electron sponge described in this invention: using an inducing agent to... 18 NPs self-assemble to Au@P2Mo 18The water-oil two-phase interface formed by NPs solution and n-hexane forms a Dawson-type polyacid plasma electronic sponge nanofunctional membrane. The Dawson-type polyacid plasma electronic sponge nanofunctional membrane is then transferred to the channel end face of a membrane material with a macroporous structure and thermally fixed to obtain a composite membrane.
[0009] Among them, Au@P2Mo 18 The preparation of NPs solution includes the following steps:
[0010] (A1) Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 Preparation: Sodium molybdate dihydrate (Na₂MoO₄·2H₂O), concentrated phosphoric acid (H₃PO₄), and concentrated hydrochloric acid (HCl) were added to deionized water and boiled under reflux. After cooling to room temperature, potassium chloride solid (KCl) was added, and the mixture was refrigerated to induce crystal precipitation. The precipitate was collected by vacuum filtration, centrifugation, and washing. Potassium chloride solid was added again to cause recrystallization of the salt. The mixture was refrigerated, and the precipitated product was separated. The product was washed successively with ethanol and anhydrous diethyl ether, and then dried under vacuum to obtain the product Dawson-type octadecylmolybdenum diphosphate (P₂Mo). 18 );
[0011] (A2) Au@P2Mo 18 Preparation of NPs dispersion: First, Dawson type octadecylmolybdenum diphosphate (P2Mo) was prepared. 18 The substance is dissolved in water, reduced by adding isopropanol under ultraviolet light, and then mixed with an aqueous solution of Au NPs to obtain Au@P2Mo. 18 NPs solution.
[0012] In step (A1), the mass ratio of sodium molybdate dihydrate, concentrated phosphoric acid, concentrated hydrochloric acid and potassium chloride (potassium chloride used for the first precipitation) is (4-4.64):1:(1.69:4-4.64), preferably 4.64:1:1.69:4.64; the boiling and reflux time is 20-30 min.
[0013] In step (A2), the preparation of the Au NPs aqueous solution includes the following steps:
[0014] (B1) Preparation of gold seed dispersion: Dissolve trisodium citrate in ultrapure water and stir. Add HAuCl4 aqueous solution to the solution and stir thoroughly. Quickly inject sodium borohydride aqueous solution and stir vigorously until the solution turns orange to obtain gold seed dispersion.
[0015] (B2) Preparation of aqueous dispersion of gold nanoparticles: The aqueous solution of HAuCl4 was heated to boiling. Under boiling conditions, gold seed dispersion and trisodium citrate aqueous solution were added in sequence. When the liquid phase gradually turned into a stable wine red color and no longer changed color, the heating was stopped. The solution was naturally cooled to room temperature under stirring to obtain an aqueous solution of Au NPs.
[0016] In step (B1), the concentration of the HAuCl4 aqueous solution is 5-30 mM, preferably 10 mM; the mass ratio of trisodium citrate to water is 1-3:20, preferably 1.47:20; the concentration of the sodium borohydride aqueous solution is 0.05-0.2 M, preferably 0.1 M; the volume ratio of the trisodium citrate aqueous solution, HAuCl4 aqueous solution, and sodium borohydride aqueous solution is 20:(0.1-1):(0.3-1.2), preferably 20:0.5:0.6; and the particle size of the gold seeds is 5-10 nm. In step (B2), the concentration of the HAuCl4 aqueous solution is 0.1-1 mM, preferably 0.3 mM; the concentration of the trisodium citrate aqueous solution is 5-20 mg / mL, preferably 10 mg / mL; and the volume ratio of the HAuCl4 aqueous solution, gold seed solution, and trisodium citrate aqueous solution is 201:(1-3):(1.6-6.4), preferably 201:1.5:3.2.
[0017] In step (A2), Dawson-type octadecylmolybdenum diphosphate (P2Mo) 18 The mass ratio of isopropanol to Au NPs is (1-3):(0.2-1):8, preferably 2:0.22:8; the UV reduction time is 25-35 min, preferably 30 min; within this range, Dawson-type octadecylmolybdenum diphosphate (P2Mo) 18 It achieves adequate reduction while maintaining electron storage capacity, and avoids the precipitation and aggregation of multiple acids.
[0018] The heat-fixing temperature is 65-75 ℃, and the heat-fixing time is 1.5-2.5 h, preferably 70 ℃ for 2 h.
[0019] The present invention relates to the application of the Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane in the purification and separation of hydrogen in mixed gases.
[0020] The mixed gas is produced by methane steam reforming, with H2 molar content ranging from 10% to 90%. The mixed gas contains H2, CO2, and CH4, and water vapor is also permitted. Operating conditions are ambient pressure and room temperature, excited by a 532 nm light source with a light power density of 50-220 mW / cm², enabling the separation of binary or ternary H2 / CO2 and H2 / CH4 mixed gases.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention has Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 The plasma-electron sponge hydrogen purification composite membrane includes a self-assembled Dawson-type octadecylmolybdenum diphosphate (P2Mo) 18 Plasma electron sponge membrane, Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 (1) The plasma electron sponge membrane has stable performance, is environmentally friendly, and has a simple preparation method with mild and easy-to-implement conditions, overcoming the shortcomings of existing technologies such as complex processes and poor controllability. (2) The present invention is a Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 Plasma-electron sponge hydrogen purification composite membranes have significant advantages in hydrogen purification applications:
[0022] 1) Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 The number of redox active sites is significantly greater: P2Mo 18 It has a 2:18 configuration, composed of two {PMo9} half-units joined together, and the number of individual clusters is much higher than that of Keggin-PMo. 12 The reversible redox sites are located within the Au nanoparticles. Under the same illumination conditions, more plasma hot electrons from the Au nanoparticles can be captured and stored, resulting in a higher electron density on the membrane surface. This leads to stronger electrostatic repulsion against highly polarized CO2, directly resulting in an order-of-magnitude improvement in separation selectivity. This is the fundamental reason why this invention can achieve high gas selectivity.
[0023] 2) This invention utilizes a liquid-liquid two-phase interface self-assembly method to construct Au@P2Mo 18 Plasma electronic sponge functional membranes are produced under mild processing conditions, requiring no high-temperature sintering. The thickness of the functional layer can be controlled by adjusting the number of membrane transfers, making the process manageable.
[0024] 3) Under illumination, gold nanoparticles generate localized surface plasmon resonance, leading to the directional transfer and storage of hot electrons in a regulated polyacid electron sponge, significantly increasing the electron density on the membrane surface. Based on the difference in gas molecule polarizability, high-polarizability CO2 is suppressed from permeation due to electrostatic repulsion, while low-polarizability H2 can pass through the membrane smoothly, achieving efficient hydrogen purification. Separation performance can be switched between dark and light conditions. P2Mo (octadecylmolybdenum diphosphate) with high electron storage capacity is selected. 18 Under illumination, the ideal selectivity of H2 / CO2 can reach up to 469. For the H2 / CO2 / CH4 test of the ternary gas mixture, the selectivity of H2 / CO2 is 408 and the selectivity of H2 / CH4 is 431.
[0025] 4) The composite membrane of this invention is resistant to water vapor and maintains high separation performance even under humid conditions. Attached Figure Description
[0026] Figure 1 The Dawson-type octadecylmolybdenum diphosphate (P2Mo) in Example 1 18 A schematic diagram of the preparation process of the plasma-electronic sponge hydrogen purification composite membrane;
[0027] Figure 2 The Dawson-type octadecylmolybdenum diphosphate (P2Mo) prepared in Example 1 18 Cross-sectional scanning electron microscope image of the plasma-electron sponge hydrogen purification composite membrane; the right image is a magnified view of a portion of the left image.
[0028] Figure 3 The Dawson-type octadecylmolybdenum diphosphate (P2Mo) prepared in Example 1 18 Figure 1 shows a planar scanning electron microscope (SEM) image of the plasma-electron sponge hydrogen purification composite membrane; Figure 2 shows the SEM image of the top of the composite membrane, and Figure 3 shows the elemental distribution map of the energy-dispersive X-ray diffraction (EDXRD) spectrum.
[0029] Figure 4 Scanning electron microscope images and elemental distribution diagrams of plasma electron sponge hydrogen purification composite membranes with different polyacid modifications in Comparative Example 1 are shown; where A is Keggin-type phosphotungstic acid, B is Keggin-type vanadium phosphate, and C is Keggin-type dodecamolybdate phosphate.
[0030] Figure 5 This is a schematic diagram of the gas membrane separation device used in Example 2;
[0031] Figure 6 The graphs show the H2 and CO2 permeability and H2 / CO2 selectivity of the composite membranes prepared with different polyacids in Example 2 under dark and light conditions.
[0032] Figure 7 This is a graph showing the H2 / CO2 selectivity of the pure AAO supported membrane in Example 2 under dark and light conditions;
[0033] Figure 8 The Dawson-type octadecylmolybdenum diphosphate (P2Mo) in Example 3 18 Stability test curve of plasma-electronic sponge hydrogen purification composite membrane under alternating dry and wet conditions;
[0034] Figure 9 The plasma-electron sponge hydrogen purification composite membrane prepared for different polyacid species in Example 3, and the selectivity of the ternary mixed gas under light irradiation.
[0035] Figure 10 Example 5 shows Dawson-type octadecylmolybdenum diphosphate (P2Mo) with different thicknesses. 18 Performance diagram of the hydrogen purification composite membrane of plasma electron sponge. Detailed Implementation
[0036] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0037] Example 1: Dawson-type octadecylmolybdenum diphosphate (P2Mo) 18 Preparation of plasma-electron sponge hydrogen purification composite membrane
[0038] (1) Synthesis of gold seeds: 1.47 mg of trisodium citrate was dissolved in 20 mL of ultrapure water. 0.5 mL of 10 mM HAuCl4 aqueous solution was added while stirring. After thorough mixing, 0.6 mL of 0.1 M sodium borohydride aqueous solution was quickly added. The solution was stirred vigorously until it turned orange to obtain a gold seed solution with a gold seed particle size of 5 nm.
[0039] (2) Preparation of Au NPs with a particle size of 35 nm: After boiling 201 mL of 0.3 mM HAuCl4 aqueous solution, 1.5 mL of the gold seed solution from step (1) and 3.2 mL of trisodium citrate aqueous solution with a concentration of 10 mg / mL were added sequentially. After the solution gradually changed from colorless to wine red and did not change color, the heater was turned off and allowed to cool naturally to room temperature under stirring to obtain an aqueous solution of Au NPs. The Au NPs were analyzed by transmission electron microscopy and the particle size of Au NPs was found to be 35 nm.
[0040] (3) Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 Preparation: 20 g of sodium molybdate dihydrate (Na₂MoO₄·2H₂O), 3 mL of concentrated phosphoric acid (H₃PO₄), and 16.5 mL of concentrated hydrochloric acid (HCl) were added to 50 mL of deionized water and mixed, then boiled under reflux for 8 h. After cooling to room temperature, 20 g of potassium chloride solid (KCl) was added to the system. The solution was refrigerated at 5 °C overnight for 12 h to induce crystal precipitation. The precipitate was collected by suction filtration using a Buchner funnel, and then redissolved in deionized water. The resulting solution was filtered to remove insoluble impurities, and then 10 g of potassium chloride solid was added to cause the salt to recrystallize again. The mother liquor and supernatant were again allowed to stand overnight at 5 °C for 12 h. Finally, the precipitated salt product was separated and washed successively with ethanol and anhydrous diethyl ether. The product was then vacuum dried at 25 °C for 12 h to obtain the product Dawson type octadecylmolybdenum diphosphate (P₂Mo). 18 ).
[0041] (4) Au@P2Mo 18 Preparation of NP dispersion: First, 0.3605g of Dawson type octadecylmolybdenum diphosphate (P2Mo) was added... 18The raw material was dissolved in 8 mL of water, and then 0.88 mL of isopropanol was added to the aqueous solution. The polyacid was photoreduced by irradiation with ultraviolet light at a wavelength of 532 nm and an intensity of 220 mW·cm⁻² for 30 min. After the photoreduction was completed, the treated polyacid solution was mixed with 32 mL of Au NPs aqueous solution from step (2). After mixing, Au@P₂Mo with a concentration of 22.2 mM was obtained. 18 NPs aqueous solution.
[0042] (5) Interfacial self-assembly into a film: Take 30 mL of Au@P2Mo 18 For the NPs aqueous solution, 5 mL of n-hexane was slowly added dropwise along the inner wall of the reaction vessel to Au@P2Mo. 18 The NPs solution is added to the upper part of the aqueous phase. Vigorous shaking is prohibited during the dropwise addition process to prevent emulsification and the formation of an emulsion. Hexane, with a lower density than water, floats on top of the aqueous phase, forming a clearly defined water-oil two-phase system. Anhydrous ethanol is used as an interface inducer; 20 mL of anhydrous ethanol is slowly injected into the aqueous solution using a pipette, maintaining the water-oil two-phase separation throughout the process. After injection, the mixture is allowed to stand for 30 minutes, during which the two phases self-assemble into a Dawson-type octadecylmolybdenum diphosphate (P2Mo). 18 Plasma-electronic sponge nanofunctional membrane.
[0043] (6) Preparation of Aluminum Oxide (AAO): First, aluminum foil was ultrasonically cleaned with acetone and 1 M KOH for 10 minutes each, and then rinsed with water. The first anodizing was performed using 0.3 M oxalic acid as the electrolyte at 45 V for 30 minutes. To eliminate the irregular oxide layer formed, the aluminum foil was treated with a mixed acid solution of 6 wt% H3PO4 and 1.8 wt% H2CrO4 at 60 °C for 40 minutes. Subsequently, the second anodizing was performed for 4 hours under the same conditions as the first anodizing. The aluminum substrate was removed with a saturated SnCl2 solution. The AAO film was treated with 1.8 wt% H3PO4 solution for 40 minutes to remove the barrier layer. The prepared AAO film was then immersed in hydrogen peroxide solution (30% H2O2) and boiled for 30 minutes, resulting in a large number of hydroxyl groups on the channel surface. Finally, the AAO film was soaked in water overnight and dried. The pore size of the nanochannels in the anodic aluminum oxide (AAO) film can be controlled by adjusting the oxidation voltage. Scanning electron microscopy analysis of the AAO film revealed a pore size of 70 nm.
[0044] (6) Film transfer-thermal bonding: Clamping the AAO film, the Dawson type octadecylmolybdenum diphosphate (P2Mo) obtained by interfacial self-assembly is transferred to the film. 18 The plasma-electron sponge nanofiber membrane is uniformly lifted from below the liquid surface, allowing Dawson-type octadecylmolybdenum diphosphate (P2Mo) to be extracted.18 Plasma-electron sponge nanofibers were completely and smoothly coated on the end face of the AAO membrane channel, resulting in a composite separation membrane with uniformly loaded functional membranes. Heat-bonding was performed in a 70 ℃ oven for 2 h to obtain a Dawson-type octadecylmolybdenum diphosphate (P2Mo) with a functional layer thickness of 127 nm. 18 Plasma-electron sponge hydrogen purification composite membrane (Au@P2Mo) 18 / AAO). The entire preparation process is as follows: Figure 1 As shown.
[0045] The preparation of Dawson-type octadecylmolybdenum diphosphate (P2Mo) in this embodiment 18 The plasma-electron sponge hydrogen purification composite membrane was characterized by cross-sectional and planar scanning electron microscopy. The results showed that the Dawson-type octadecylmolybdenum diphosphate (P2Mo) 18 The plasma-electron sponge functional layer completely covers the surface of the AAO membrane cross-section. The functional layer is tightly bonded to the AAO substrate, with uniform coverage and no obvious defects or exposed substrate areas. The results are as follows: Figure 3 .
[0046] Comparative Example 1
[0047] The experimental procedure is the same as steps (4)-(6) in Example 1, except that the polyacid raw material Dawson type octadecylmolybdenum diphosphate (P2Mo) is replaced in step (4). 18 These are Keggin-type phosphotungstic acid (H3PW) 12 O 40 PW (abbreviated as PW) 12 ), Keggin-type vanadium phosphoric acid (PV) 14 ), Keggin-type octadecylmolybdenum diphosphate (PMo) 12 Au@PW were obtained respectively. 12 / AAO composite film, Au@PV 14 / AAO composite membrane and Au@PMo 12 / AAO composite membrane.
[0048] The composite film prepared in this comparative example was analyzed by scanning electron microscopy, and the results are as follows: Figure 4 .Depend on Figure 4 It can be seen that the plasma electron sponge functional layers constructed from different Keggin-type polyacids are all tightly and continuously covered on the top of the AAO nanochannels, and the film thickness is stable, indicating that this type of composite membrane can be successfully prepared by different polyacid systems.
[0049] Example 2 Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 Performance testing of plasma-electron sponge hydrogen purification composite membrane gas separation
[0050] (1) Dawson-type octadecylmolybdenum diphosphate (P2Mo) prepared using Example 1 18 Plasma-electron sponge hydrogen purification composite membrane separation of hydrogen and carbon dioxide mixed gases, gas separation device such as Figure 5 As shown, argon gas was introduced at a flow rate of 10 mL / min as the purge gas, and a mixture of hydrogen and carbon dioxide was introduced, with the total volumetric flow rate maintained at 60 mL / min (hydrogen / carbon dioxide at 30 / 30 mL / min). The system can be divided into a feed gas side and a permeate gas side. The permeate gas was delivered to an online gas chromatograph (Panna) for quantitative detection. A 532 nm laser with a power density of 220 mW / cm² was used as the light source. The test temperature was 25 ℃, and the total system pressure was 100 kPa.
[0051] Simultaneously, Au@PW prepared using Comparative Example 1 12 / AAO composite film, Au@PV 14 / AAO composite membrane and Au@PMo 12 / AAO composite membrane and 70nm pore size pure anodic alumina support membrane to replace Dawson type octadecylmolybdenum diphosphate (P2Mo) 18 The plasma-electron sponge hydrogen purification composite membrane was tested under both dark and light conditions, with all other test conditions remaining unchanged. The test results are shown in [see figure]. Figures 6-7 .Depend on Figure 6 It can be seen that Au@P2Mo 18 / AAO composite membrane: H2 / CO2 selectivity 77 under dark conditions; H2 / CO2 selectivity 469 under light conditions; Au@PMo 12 / AAO composite membrane: H2 / CO2 selectivity 69 under dark conditions; H2 / CO2 selectivity 301 under light conditions; Au@PW 12 / AAO composite membrane: H2 / CO2 selectivity 55 under dark conditions; H2 / CO2 selectivity 260 under light conditions; Au@PV 14 / AAO composite membrane: H2 / CO2 selectivity 71 under dark conditions; H2 / CO2 selectivity 374 under light conditions; indicating that Dawson-type polyacids significantly alter the membrane's hydrogen purification and separation performance compared to Keggin-type polyacids; Au@P2Mo 18 The / AAO composite membrane exhibited optimal separation performance, confirming the P2Mo... 18 Molecules are the source of high performance.
[0052] Depend on Figure 7 It is evident that the H2 / CO2 selectivity of the pure AAO membrane under illumination is only 1.3, while the selectivity under darkness is 1.2. The pure AAO membrane lacks a plasma-polyacid functional layer and therefore has no light-controlled separation effect.
[0053] Example 3: Long-term stability test of composite membrane under water vapor conditions
[0054] The experimental procedure was the same as in Example 2, but Au@P2Mo prepared in Example 1 was selected. 18 / AAO's composite membrane underwent a wet-dry alternating stability test. Using a 30:30 volume ratio of H2 / CO2 as the feed gas, the membrane was subjected to a wet-dry alternating durability test for a total duration of 88 h at 25 ℃ and a feed pressure of 0.15 MPa. The experiment employed a periodic switching strategy: a dry H2 / CO2 mixture was alternately fed with a H2 / CO2 mixture of the same ratio carrying 2.5 vol% water vapor, with a single-stage aeration time of 11 h, and the cycle was repeated. The total feed flow rate was 60 mL·min⁻¹, and the argon purge gas flow rate was 10 mL·min⁻¹. Samples were taken periodically, and the permeate-side gas composition was analyzed using gas chromatography to monitor changes in membrane permeate flux and separation selectivity over time. The experimental results are as follows: Figure 8 .Depend on Figure 8 It can be seen that after the dry-wet cycle, Au@P2Mo 18 The H2 permeability of the / AAO composite membrane decreased slightly, but the H2 / CO2 selectivity remained above 423, indicating that Au@P2Mo 18 / AAO composite membrane has water vapor resistance.
[0055] Example 4: Comparison of Three-way Gas Mixture Separation Performance
[0056] The experimental procedure was the same as in Example 2. The composite membranes prepared in Example 1 and Comparative Example 1 were tested under a ternary simulated reforming hydrogen production mixed gas condition of H2 / CO2 / CH4. The molar ratio of the mixed gas was H2:CO2:CH4 = 7:2:1, the test temperature was 25℃, the total pressure was 100kPa, and the optical power density of the 532nm light source was 220 mW / cm². 2 The hydrogen permeability, H2 / CO2 selectivity, and H2 / CH4 selectivity of each composite membrane were recorded under illumination conditions. The test results are as follows: Figure 9 Au@P2Mo 18 / AAO composite membrane: Under illumination, the H2 / CO2 selectivity of the ternary gas mixture is 408, and the H2 / CH4 selectivity is 431; Au@PMo 12 / AAO composite membrane: Under illumination, the H2 / CO2 selectivity of the ternary gas mixture is 241, and the H2 / CH4 selectivity is 260; Au@PW 12 / AAO composite membrane: Under illumination, the H2 / CO2 selectivity of the ternary gas mixture is 210, and the H2 / CH4 selectivity is 234; Au@PV 14 / AAO composite membrane: Under illumination, the H2 / CO2 selectivity of the ternary gas mixture is 374, and the H2 / CH4 selectivity is 416; Au@P2Mo18 / AAO exhibits the best separation performance, far superior to other composite membranes, indicating that the Dawson-type octadecylmolybdenum diphosphate (P2Mo) exhibits the best separation performance. 18 Compared to Keggin-type phosphotungstic acid, Keggin-type vanadium phosphoric acid, and Keggin-type dodecamolybdenum phosphoric acid, it exhibits superior separation performance in ternary gas mixtures.
[0057] Example 5: Dawson-type octadecylmolybdenum diphosphate (P2Mo) with different thicknesses 18 Preparation of a hydrogen purification composite membrane using plasma-electron sponge
[0058] The experimental procedure was the same as in Example 1. Compared with Example 1, the Dawson-type octadecylmolybdenum diphosphate (P2Mo) in step (6) of Example 1 was changed. 18 Plasma-electron sponge films were transferred 1-4 times, resulting in Dawson-type octadecylmolybdenum diphosphate (P2Mo) nanofilms with thicknesses of 40±5 nm, 130±5 nm, 190±5 nm, and 250±5 nm. 18 Plasma-electron sponge nanochannel composite membranes were developed. Argon was used as the purge gas at a flow rate of 10 mL / min, and a hydrogen / carbon dioxide mixture was introduced, maintaining a total volumetric flow rate of 60 mL / min (hydrogen / carbon dioxide ratio of 30 / 30 mL / min). The system can be divided into a feed gas side and a permeate gas side. The permeate gas was sent to an online gas chromatograph (Panna) for quantitative detection. A 532 nm laser with a power density of 220 mW / cm² was used as the light source. The test temperature was 25 ℃, and the total system pressure was 100 kPa. The hydrogen permeability and H₂ / CO₂ selectivity of each composite membrane under these conditions were recorded. The test results are as follows: Figure 10 Au@P2Mo nanofibers with a thickness of 40±5 nm were plasma-enhanced electron sponge nanofilms. 18 / AAO composite film: H2 / CO2 selectivity 47 under illumination; Au@P2Mo nanofilm with a thickness of 130±5 nm under plasma electron sponge nanofilm thickness. 18 / AAO composite membrane: H2 / CO2 selectivity 469 under illumination; Au@P2Mo nanofiber functional membrane with a thickness of 190±5 nm under plasma electron sponge illumination. 18 / AAO composite film: H2 / CO2 selectivity 420 under illumination; Au@P2Mo plasmonic electronic sponge nanofilm with a thickness of 250±5 nm. 18 / AAO composite membrane: H2 / CO2 selectivity 399 under illumination; among which, the Dawson-type octadecylmolybdenum diphosphate (P2Mo) with a thickness of 130±5 nm is a plasma-enhanced electron sponge nanofilm.18 The plasma-electron sponge hydrogen purification composite membrane exhibited the best separation effect.
Claims
1. A Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane, characterized in that, It includes a Dawson-type polyacid plasma electronic sponge nanofunctional membrane and a macroporous structure support membrane. Some pores of the Dawson-type polyacid plasma electronic sponge membrane are connected to some macropores of the macroporous support membrane.
2. The Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane according to claim 1, characterized in that, Dawson-type polyacid plasma-electron sponge nanofiber membrane is composed of plasma nanoparticles and Dawson-type polyacids capable of storing electrons.
3. The Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane according to claim 1, characterized in that, The thickness of the Dawson-type polyacid plasma electron sponge nanofiber functional membrane is 40-250 nm.
4. The Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane according to claim 2, characterized in that, The plasma nanoparticles are gold nanoparticles with a particle size of 5-35 nm.
5. The Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane according to claim 2, characterized in that, The electron-storing Dawson-type polyacid is selected from octadecylmolybdenum diphosphate, and the macroporous structure support membrane is anodized aluminum oxide membrane with a pore size of 40-100 nm.
6. The method for preparing the plasma electron sponge hydrogen purification composite membrane with Dawson-type polyacid as the core electron sponge as described in any one of claims 1-5, characterized in that, Using an inducing agent to transfer Au@P2Mo 18 NPs self-assemble to Au@P2Mo 18 The water-oil two-phase interface formed by the NPs solution and n-hexane forms a Dawson-type polyacid plasma electronic sponge nanofunctional membrane. The Dawson-type polyacid plasma electronic sponge nanofunctional membrane is then transferred to the channel end face of a membrane material with a macroporous structure and thermally fixed.
7. The preparation method according to claim 6, characterized in that, Au@P2Mo 18 The preparation of NPs solution includes the following steps: (1) Preparation of Dawson type octadecylmolybdenum diphosphate: Sodium molybdate dihydrate, concentrated phosphoric acid and concentrated hydrochloric acid were added to deionized water and boiled under reflux; cooled to room temperature, potassium chloride was added, and the mixture was refrigerated to induce crystal precipitation. The precipitate was collected by vacuum filtration, centrifugation and washing, potassium chloride solid was added to cause reprecipitation, and the product was refrigerated to separate the precipitate. The product was washed with ethanol and anhydrous diethyl ether in sequence, and dried under vacuum to obtain the product Dawson type octadecylmolybdenum diphosphate. (2) Au@P2Mo 18 Preparation of NPs dispersion: Dawson-type octadecylmolybdenum diphosphate was first dissolved in water, then isopropanol was added, and the mixture was reduced under ultraviolet light. Au NPs aqueous solution was then added and mixed thoroughly to obtain Au@P2Mo. 18 NPs solution.
8. The preparation method according to claim 7, characterized in that, In step (1), the mass ratio of sodium molybdate dihydrate, concentrated phosphoric acid, concentrated hydrochloric acid and potassium chloride is (4-4.64):1:(1.69:4-4.64), and the boiling and reflux time is 20-30 min.
9. The preparation method according to claim 7, characterized in that, In step (2), the mass ratio of Dawson type octadecylmolybdenum diphosphate, isopropanol and Au NPs is (1-3):(0.2-1):8; the UV reduction time is 25-35 min.
10. The application of the Dawson-type multi-acid plasma electron sponge hydrogen purification composite membrane according to any one of claims 1-5 in the purification and separation of hydrogen in mixed gases.